Hubungan Pengetahuan Ibu Dengan Deteksi Keterlambatan Bicara (Speech Delay) Pada Balita 1-3 Tahun - Sulistyana, Anik; Pramono, Joko Sapto; Suryani, Heni; Era, Dwi Prihatin (Akademi Kebidanan Bunga Husada Samarinda, 2024)
Speech delay or late speech is one of the disturbances in the stages of child development. Initial observations in the working area of the Rantau Hempang Muara Kaman sub-district health center found children who were considered to have speech disorders. The aim was to determine the relationship between mother's knowledge and speech delay detection in toddlers 1-3 years old. This type of research is an analytic survey with a cross-sectional design. The population is mothers who have toddlers aged 1-3 years who come to Posyandu Lestari which is the working area of the Rantau Hempang auxiliary health center as many as 61 people. The sampling technique is total sampling, so the sample is 61 people. Data analysis used the chi-square test. Most of the characteristics of mothers aged between 22-35 years (83.6 percent), mother's education graduated from junior high school (45.9 percent), mother's work as housewife (62.3 percent), child age 2 years (44.3 percent) ), male sex (54.1 percent), the order of the 1st and 2nd children (31.1 percent), the number of siblings is 1 person (36.1 percent) and the number of family members is 4 people (31, 1 percent). Most mothers' knowledge about speech delay detection was sufficient (45.9 percent) and the detection of speech delay in children 1-3 years was mostly good (65.6 percent). The value of the Chi square test results is obtained p value: 0.010 less than α : (0,05). There is a relationship between mother's knowledge and speech delay detection in toddlers 1-3 years.